FORENSIC TOXICOLOGY AT THE INTERSECTION OF DRUGS OF ABUSE AND PUBLIC HEALTH - Xavier, Lucas Dornas; Vargas, Lucas Albanaz; da Silva, Davi Nunes; de Oliveira, Andressa Carvalho (Seven Editora, 2026)
Forensic toxicology applies scientific knowledge to identify and analyze toxic substances in legal and public health contexts, and is fundamental to combating drugs of abuse. These include legal substances such as alcohol and tobacco, and illegal substances such as cocaine, derivatives like crack, and new psychoactive substances (legal highs), which have serious consequences for health and society. The objective of this scientific study was to review the contributions and updates of forensic toxicology, highlighting its importance for public health and justice. The methodology involved a literature review in databases such as PubMed and LILACS, considering studies from the last 20 years and focusing on techniques and advances in the field. Forensic toxicology has evolved since the 19th century, with the development of methods such as chromatography and mass spectrometry, which allow for precise analyses in biological matrices such as blood and urine. Techniques such as immunochromatography have demonstrated efficiency in drug screening, while information systems monitor cases of intoxication and underreporting. The analysis of crack cocaine, for example, highlights its devastating impact and the importance of rigorous methods such as thin-layer chromatography. Controlling new drugs requires international collaboration and dynamic legislation. Forensic toxicology is considered essential for monitoring substances, identifying consumption patterns, and informing public policies, being indispensable for addressing the problem of drug abuse and protecting the health and safety of society. DOI: https://doi.org/10.56238/sevened2026.008-105